PENGGUNAAN GAYA BAHASA PADA MEDIA BERITA ONLINE KOMPAS - Hartati Hartati; Haedariah Haedariah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The formulation of the problem in this study is what language styles are used in online news media in Kompas. This study aims to describe what language styles are used in online news media in Kompas. The method used is a qualitative method where the application of this qualitative method is descriptive, meaning that the data produced is in the form of words in the form of quotations. The data in this study is in the form of language exposure, namely words, phrases. The source of this research is news published in the Kompas Online mass media editions, June and July, August and September 2024. The data collection technique used in the study is the document review technique or commonly called a documentation study. This research was analyzed using a Sociolinguistic approach. It can be concluded that the language style contained in the Kompas Online News Media, which consists of twenty-two quotations found by researchers which are divided into several parts, namely, Synecdoche Language Style, Epithet Language Style, Metaphor Language Style, Simile Language Style, Ellipsis Language Style, Irony Language Style, Figurative Language Style, Personification Language Style, Hyperbole Language Style. Therefore, it is suggested that further researchers also conduct in-depth research from the perspective of literary studies or others.